2011
DOI: 10.1088/0034-4885/74/11/116501
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear elasticity in nanostructured materials

Abstract: We elaborate on a blended continuum/atomistic theoretical picture of the nonlinear elastic properties of nanostructured materials, looking at diverse aspects such as dispersions of inhomogeneities within a matrix, random or graded nanograined materials, two-dimensional atomic sheets. In particular, we discuss the possible onset of length-scale effects and we establish the limits and merits of continuum versus atomistics. While most situations here discussed correspond to model systems, the main conclusions hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 99 publications
(202 reference statements)
2
57
0
Order By: Relevance
“…It is observed that the interlayer stress reverses when shock wave reflects on the graphene interface, which can verify the approximate free boundary condition. Though the graphene is strongly nonlinear for relatively large strain, 2,25 it is found that the actual strain in graphene is small during the shock wave propagating due to the free boundary effect. Thus, the nonlinear effect here does not play an important role on the wave propagation, which is also consistent with the previous research about Kurdjumov-Sachs interface.…”
mentioning
confidence: 99%
“…It is observed that the interlayer stress reverses when shock wave reflects on the graphene interface, which can verify the approximate free boundary condition. Though the graphene is strongly nonlinear for relatively large strain, 2,25 it is found that the actual strain in graphene is small during the shock wave propagating due to the free boundary effect. Thus, the nonlinear effect here does not play an important role on the wave propagation, which is also consistent with the previous research about Kurdjumov-Sachs interface.…”
mentioning
confidence: 99%
“…The coupling problem can be approached and solved by means of the multi-physics Eshelby formalism [32,31,30,15]. As recently verified [15], the local stress depends on the external electric and elastic fields and on the magnetization direction.…”
Section: Coupling With the External Electric And Elastic Fieldsmentioning
confidence: 95%
“…Nevertheless, we may now consider an arbitrary size of the particle. To explain this point we recall an important property of the Eshelby theory (which is valid for the case with any possible coupling): when an ellipsoidal particle is embedded in an infinite matrix and subjected to uniform external actions, the physical fields (electric, magnetic and elastic) induced within the particle itself are always uniform and they depend on the material properties of the two phases and on the ratios a 1 /a 2 and a 2 /a 3 [32,31,30,15,47,48,49]. The internal fields do not depend on the actual size of the particle: only the shape of the ellipsoid may influence the particle response.…”
Section: Switching Process Within the Magnetoelectric Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (1) is valid for |σ| ≤ σ max . It is demonstrated in [2] and [3] that the material constant D depends on the direction considered on the graphene plane.…”
Section: Introductionmentioning
confidence: 99%